Kinerja internal reboiler tipe vertical tubular baffle pada proses distilasi etanol secara batch - Yuana Susmiati; Bambang Purwantana; Nursigit Bintoro; Sri Rahayoe (Jurnal Rekayasa Proses, 2021)
The performance of ethanol distillation is determined by the type of reboiler used in the distillation column. This study aims to determine the effect of differences in diameter and height of internal reboiler tubes, as well as feed content on ethanol distillate concentration and distillation yield. The research was conducted on a batch ethanol distillation process using a rectified distillation device with an internal vertical tubular baffle reboiler using different diameters and tube height, namely 1.5, 1, and 0.5 inches of diameter, and 8, 6, and 4 cm of tube heights. Materials or feeds in this study were ethanol solutions with levels of 10%, 20%, and 30% v/v. The results showed that the highest ethanol distillate content of 97.17% v/v (average) was achieved in the distillation process using an internal reboiler with a diameter of 0.5”, a tube height of 8 cm, and a feed content of 10%. Geometry affected the heat transfer process in the internal reboiler of a distillation device so that it affected the distillation results.